Strategi Guru BK dalam Membantu Perencanaan Karir Siswa Sekolah Menengah Atas: Systematic Literature Review - Ainun Nur Fitri Ramdhiani; Melda Ananda Putriani; Falia Nur Arviani; Calien Rizki Adnindia; Kholil Lur Rochman (STIKes Ibnu Sina Ajibarang, 2025)
Career planning is an important thing that students need to prepare early on to face the increasingly competitive world of work. Guidance and Counseling (BK) teachers have an important role in helping students design and prepare their careers. This study uses the Systematic Literature Review (SLR) method by reviewing six relevant journals regarding BK teacher strategies in helping high school (SMA) students plan their careers. The purpose of this study is to describe effective strategies in career guidance services in schools. The results of the study indicate that various strategies, such as mapping students' career interests, using animated video media, career information services through digital media, and career skills training, can help students understand their potential, increase motivation, and determine the right career choices. By implementing appropriate and innovative strategies, BK teachers can be more optimal in assisting students in their career planning.